A study into the effect of Lactobacillus casei Shirota in preventing antibiotic associated diarrhoea including Clostridioides difficile infection in patients with spinal cord injuries: a multicentre randomised, double-blind, placebo-controlled trial. (October 2021) - Wong, Samford; Hirani, Shashivadan P; Forbes, Alastair; Kumar, Naveen; Hariharan, Ramaswamy; O'Driscoll, Jean; Viswanathan, Anand; Harvey, Graham; Sekhar, Ravi; Jamous, Ali
Abstract: Background: Antibiotic Associated Diarrhoea (AAD) and Clostridioides Difficile Infection (CDI) are of major concern in spinal cord injury (SCI) rehabilitation. Methods: A multi-centre, randomized, double-blind, placebo-controlled (the ECLISP) trial, was conducted in three tertiary spinal cord injury centre in the UK to assess the efficacy of consuming a probiotic beverage containing at least 6.5 × 10 9 live Lactobacillus casei Shirota (LcS) in preventing AAD and CDI and in patients with SCI and to determine whether proton pump inhibitors (PPI) and under nutrition-risk are risk factors for AAD/CDI. LcS or placebo was given once daily for the duration of an antibiotic course and continued for 7 days thereafter. Follow up was set at 7 and 30 days after the antibiotic course finished. The primary outcome was occurrence of AAD up to 30 days after finishing LcS/placebo. This trial is completed and registered (ISRCTN:13119162). Findings: Between November 2014, and November 2019, 359 consenting adult SCI patients (median age: 53.3; range: 18–88 years), from 3 SCI centres responsible for providing approximate 45–50% of UK SCI service, with a requirement for antibiotics due to infection were randomly allocated to receive LcS ( n  = 181) or placebo ( n  = 178). Overall, no statistical difference was seen in occurrence of the primary outcomes of AAD at 30 days follow up (45% v 42.1%, RR: 1.071, 0.8-1.4, p = 0.639). In the secondary analyses LcS was associated with a lower risk of AAD at 7 (19% v 35.7%, RR: 0.53, 0.29–0.99, p  = 0.040) and 30 days follow up (28% v 52.2%, RR: 0.54, 0.32–0.91, p  = 0.015) in the participants who took PPI regularly. Under nutrition-risk was associated with an increased risk of AAD at 7 (RR: 1.76, 1.28–2.44) and 30 days follow up (RR: 1.69, 1.30–2.0). No intervention-related adverse events were reported during the study. Interpretation: The present study indicates that LcS could not prevent AAD/CDI in unselected SCI patients. LcS might have the potential to prevent AAD in the higher risk group of patients on regular PPI. Confirmatory studies are needed to allow translation of this apparent therapeutic success into improved clinical outcomes. Funding: Yakult Honsha Co., Ltd.